Weldability of New Material Sandwich Steel for Automotive Applications - Abbas Al Naimi, Ihsan Kadhom (Al-Khwarizmi Engineering Journal, 2017)
Todays, World is faced an energy crisis because of a continuous increasing the consumption of fuels due to intension demand for all types of vehicles. This study is one of the efforts dealing with reduce the weight of vehicles by using a new material of sandwich steel, which consists of two skin steel sheets with core of a polymer material. Resistance spot welding (RSW) can be easily implemented on metals; however a cupper shunt tool was designed to perform the resistance welding of sandwich steel with DP800 cover sheets to resolve a non-conductivity problem of a polymer core. Numerical simulations with SORPAS®3D were employed to test the weldability of this new material and supported by many practical experiments. In conclusion, it was found that the weldability could be improved with using two pulses and optimized their welding parameters. Tensile-shearing tests were carried out to evaluate the strength of welding sheets. Macro/micrograph and SEM/EDS examinations were also carried out to analyze welding area and compare the nugget of welding sheets with different welding parameters. The concluded optimum welding parameters are; 3.5 kN, (5.5 kA, 8 cycles), and (10 kA, 5 cycles) for the electrode force, welding current and time of first and second pulse respectively.